A new genus and species of Pseudococcidae (Hemiptera: Sternorrhyncha: Coccomorpha) from China - Dong, Qin-Gang; Zhang, Jiang-Tao; Wu, San-An (Zootaxa, 2017)
A new mealybug genus, Dorsoceraricoccus Dong & Wu gen. nov. (Hemiptera: Sternorrhyncha: Coccomorpha: Pseudococcidae), is described to contain Dysmicoccus muajatae Williams as type species, and a new species, Dorsoceraricoccus ningboensis Dong & Wu sp. nov., collected from Zhejiang Province, China on Digitaria sp. (Poaceae). For the new species, the adult female is described and illustrated. In addition, a key to genera of the subfamily Pseudococcinae now known from China and a key to adult female now in Dorsoceraricoccus gen. nov. are provided.